Hot Thespian Action! 10 Premiere Plays from Walterdale Playhouse - Robin Whittaker (Canadian Plays, 2008)
In Hot Thespian Action! Robin Whittaker argues that new plays can thrive in amateur theatres, which have freedoms unavailable to professionalized companies. And he proves it with 10 relevant, engaging playscripts originally produced by one of Canada's longest-running theatres, Edmonton's acclaimed Walterdale Theatre Associates. This collection challenges notions that amateur theatre is solely a phenomenon of the pre-professional past. Whittaker makes an important contribution to Canadian theatre studies with the first North American anthology in 80 years to collect plays first produced by a nonprofessionalized theatre company. Plays by • Brad Fraser • Mary Glenfield • Warren Graves • Gordon Pengilly • Barbara Sapergia & Geoffrey Ursell • Trevor Schmidt • Jonathan Seinen • Scott Sharplin • Mark Stubbings • Wilfred Watson